Implementation of Zoning Theory Based on the Concept of Tri Hita Karana, Tri Mandala and Sanga Mandala of Mas Village, Ubud, Bali in Maintaining Cultural Values - Wahyu Nurmala, Citra; Asrofi, Muchamad Hisyam; Maqsuna, Arista Rahma; Madikha, Abidatin; Paramitha, Sabbila Arkana; Fatoni, Fikri; Virgiawan, Dhimas Bagus (Sustainability (STPP) Theory, Practice and Policy, 2025)
This study examines the implementation of zoning theory grounded in the Balinese philosophical concepts of Tri Hita Karana, Tri Mandala, and Sanga Mandala in Mas Village, Ubud, Bali, to preserve cultural values amidst rapid tourism growth. Employing a qualitative phenomenological approach within a naturalistic paradigm, the research integrates Landis’s (1958) theory of social structure and Bintarto’s (1983) spatial-economic interaction framework to analyze spatial organization. Data were collected through in-depth interviews, participatory observation, and document analysis, using snowball sampling to engage key informants, including adat leaders and community members. Findings reveal that Desa Mas effectively maintains Tri Hita Karana’s harmony (Parhyangan, Pawongan, Palemahan) through zoned spatial planning, with Utama Mandala preserving sacred spaces, Madya Mandala fostering social activities, and Nista Mandala supporting economic functions. However, tourism-driven land conversion threatens traditional zoning, shifting economic activities from artisanal crafts to commercial ventures. The study underscores the resilience of Balinese zoning principles in sustaining cultural identity, yet highlights the need for adaptive strategies to mitigate modernization’s impact. By blending traditional philosophies with modern zoning theories, this research offers insights for sustainable spatial planning in culturally sensitive tourism destinations, contributing to global discourses on cultural preservation and urban-rural dynamics.